1993
DOI: 10.1128/mcb.13.3.1796
|View full text |Cite
|
Sign up to set email alerts
|

A mitogen-responsive promoter region that is synergistically activated through multiple signalling pathways.

Abstract: A regulatory region of the human transferrin receptor gene promoter was found to be required for increased expression in response to serum or growth factors. This region contains two elements that appear to cooperate for full responsiveness. We found that sodium orthovanadate treatment of cells significantly activated expression of promoter constructs containing these elements. 12-0-Tetradecanoylphorbol-13-acetate alone induced a twofold increase in expression but acted synergistically with vanadate to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Consistent with previous reports (Agrawal et al, 1996), p27 Kip1 was expressed at high levels in quiescent 3T3 cells but gradually declined to very low levels by 12 ± 15 h after serum stimulation, the time at which the cells are entering into S phase (Ouyang et al, 1993). Surprisingly, however, no p27 Kip1 was detected in the nuclear fraction at any time point.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with previous reports (Agrawal et al, 1996), p27 Kip1 was expressed at high levels in quiescent 3T3 cells but gradually declined to very low levels by 12 ± 15 h after serum stimulation, the time at which the cells are entering into S phase (Ouyang et al, 1993). Surprisingly, however, no p27 Kip1 was detected in the nuclear fraction at any time point.…”
Section: Resultssupporting
confidence: 91%
“…6). The ICAM-1 and CD71 promoters contain many transcription factor binding sites, including both NF-κB and AP-1 sites (Ouyang et al, 1993 ;Jahnke & Johnson, 1994 ;Mun4 oz et al, 1996). In the case of ICAM-1, activation of the promoter by the antioxidant pyrrolidinedithiocarbamate has been shown to involve the AP-1 site (Mun4 oz et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these two putative TRElike elements are functional remains to be determined in future studies. Several studies have demonstrated that these TRE and TRE-like elements are able to mediate activation [27][28][29] and inhibition [30] of gene expression, depending on the cell type as well as the stage of cell growth and differentiation. Such dual regulation by the same regulatory element can reflect the concomitant binding of different transcriptional factors in different tissues [30].…”
Section: Discussionmentioning
confidence: 99%